The impact of corporate social responsibility, budget surplus, and investment cash flow on capital expenditure budgeting of Indonesian city governments - Haryanto; Faisal; Agung Juliarto; Wahyu Meiranto (Public and Municipal Finance, 2025)
This study aims to examine the impact of corporate social responsibility, budget surplus, and investment cash flow on capital expenditure budgeting within city government clusters in Indonesia. The population includes city governments recorded in the Ministry of Home Affairs. The samples were taken from data on corporate social responsibility and budget surplus, as well as investment cash flow for the fiscal year 2023 and capital expenditure budget for 2024 in 81 city governments in Indonesia. Empirical findings indicate that corporate social responsibility negatively affects capital expenditure budgeting across all city government clusters. The impact of budget surplus varies. On the one side, budget surplus has a positive effect on capital expenditure budgeting in Cluster A (highest) and a negative impact on capital expenditure budgeting in Cluster C (lowest). Conversely, in Cluster B (middle), budget surplus does not affect capital expenditure budgeting. Similarly, investment cash flow positively affects capital expenditure budgeting in Cluster A and negatively affects capital expenditure budgeting in Cluster C. Meanwhile, in Cluster B, investment cash flow does not affect capital expenditure budgeting.